The Influence of Spiritual Leadership and Self Efficacy on Work Engagement Mediated by Character Building in Students' Islamic Boarding School Organizations - Aini, Sofia Nurul; Setiani, Setiani (Li Falah: Journal of Islamic Economics and Business, 2024)
This study was conducted with the aim of analyzing and determining the effect of spiritual leadership and self-efficacy on work engagement mediated by character formation in Islamic boarding school student organizations. This study is a quantitative study with an explanatory type with a hypothesis formulation between variables. The population of the study was students of the Al-Hikmah Al-Fathimiyyah Merjosari Islamic Boarding School in Malang City. The sampling technique used was purposive sampling technique totaling 60 people. Data collection techniques used were interviews, observations, questionnaires and documentation. Data analysis used descriptive statistical analysis and SmartPLS 4.0 application techniques. Based on the hypothesis in this study, the results of the study showed that spiritual leadership had an effect but was not significant on work engagement. But for self-efficacy, it had a significant effect on work engagement. Then character formation as a mediating variable did not mediate well between spiritual leadership on work engagement and self-efficacy on work engagement